2006
DOI: 10.1309/7rqe37k6439t4pb4
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Thyroid Gland Fine-Needle Aspiration

Abstract: Scant published data exist on redesigning pathology practice based on error data. In this first step of an Agency for Healthcare Research and Quality patient safety project, we measured the performance metrics of thyroid gland fine-needle aspiration, performed root cause analysis to determine the causes of error, and proposed error-reduction initiatives to address specific errors. Eleven cytologists signed out 1,543 thyroid gland aspirates in 2 years, and surgical pathology follow-up was obtained in 364 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 27 publications
0
41
0
1
Order By: Relevance
“…Receiver operating characteristic analysis showed that all three markers improved the performance of thyroid FNA, with AUCs above 0.8 in comparison with values between 0.58 and 0.74 obtained in a recent analysis in which performance of 11 cytologists was measured using AUC (Raab et al, 2006). Comparison of the three ROC curves indicated that the sensitivity of TPO was superior to that of HBME-1 and DPP4 and its specificity was also superior to that of HBME-1.…”
Section: Discussionmentioning
confidence: 53%
“…Receiver operating characteristic analysis showed that all three markers improved the performance of thyroid FNA, with AUCs above 0.8 in comparison with values between 0.58 and 0.74 obtained in a recent analysis in which performance of 11 cytologists was measured using AUC (Raab et al, 2006). Comparison of the three ROC curves indicated that the sensitivity of TPO was superior to that of HBME-1 and DPP4 and its specificity was also superior to that of HBME-1.…”
Section: Discussionmentioning
confidence: 53%
“…Raab et al reported that such samples may be a potential source of diagnostic error in thyroid cytopathology. 23 Evaluation of air-dried CP on site from the CB tissue results in decreasing the overall number of passes with the confidence of having obtained good-quality and adequate diagnostic material. There are specific thyroid lesions in which CB/CP is especially useful.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare sensitivity, specificity, and accuracy data, because these vary between institutions, depending on the cytologic criteria and diagnostic categories used for reporting and the assignment of cytologic and histologic diagnosis during statistical calculations. By using criteria described previously 23 for IR thyroid biopsies performed during 2005 at Northwestern Memorial Hospital, our sensitivity for neoplasm/malignancy was 83%, and specificity was 69%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] It should be noted that FNAB is an invasive procedure and, in addition to the possibility of errors in sampling and analysis, this Section: Radiology method is not cost effective for studying of all nodules and the experience of the physician performing the aspiration is also important. [15][16][17] Ultrasonography is the imaging study of choice for thyroid nodules The ultrasonography (USG) is the non-invasive and is highly sensitive in assessing nodule size and number. The cost-effectiveness of USG in solving patient-specific clinical problems has not been formally tested and when used judiciously, helps to answer important clinical questions in specific patients.…”
Section: Introductionmentioning
confidence: 99%